2023
DOI: 10.1101/2023.01.22.525079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waning Immunity Against XBB.1.5 Following Bivalent mRNA Boosters

Abstract: The SARS-CoV-2 Omicron variant has continued to evolve. XBB is a recombinant between two BA.2 sublineages, XBB.1 includes the G252V mutation, and XBB.1.5 includes the G252V and F486P mutations. XBB.1.5 has rapidly increased in frequency and has become the dominant virus in New England. The bivalent mRNA vaccine boosters have been shown to increase neutralizing antibody (NAb) titers to multiple variants, but the durability of these responses remains to be determined. We assessed humoral and cellular immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 6 publications
8
45
0
Order By: Relevance
“…The BA.5 breakthrough cohort exhibited significantly higher NAb titers at three months against all Omicron subvariants tested when compared to both monovalent and bivalent booster cohorts ( Figure 1B ). An approximately 2-fold drop in mean NAb titers was noted for the vaccine cohorts over the follow-up period of ∼2 months ( Figure 1C ), consistent with recent findings 5 . Interestingly, there was no discernible waning of antibody responses in the BA.5 breakthrough infection cases over the same observation period.…”
Section: Main Textsupporting
confidence: 89%
“…The BA.5 breakthrough cohort exhibited significantly higher NAb titers at three months against all Omicron subvariants tested when compared to both monovalent and bivalent booster cohorts ( Figure 1B ). An approximately 2-fold drop in mean NAb titers was noted for the vaccine cohorts over the follow-up period of ∼2 months ( Figure 1C ), consistent with recent findings 5 . Interestingly, there was no discernible waning of antibody responses in the BA.5 breakthrough infection cases over the same observation period.…”
Section: Main Textsupporting
confidence: 89%
“…Moreover, bebtelovimab (LY-CoV1404) and Evusheld (a combination of COV2-2196 and COV2-2130) were found to be inactive against XBB/XBB.1 [ 6 ] and XBB.1.5 [ 15 ]. Although XBB.1.5 escapes neutralizing antibody responses, a study by Lasrado et al has shown that the cross-reactive T-cell responses may continue to protect against severe disease [ 25 ]. Therefore, due to immune-escape-associated and infectivity-enhancing mutations, the XBB* and XBB.1.5 variants can eventually spread worldwide [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the approximately 2-month follow-up period, mean NAb titres in both vaccine cohorts decreased approximately two-fold (or 50%) against all tested viruses (eg, 1218 to 509 for monovalent cohorts against BA.5 and 1553 to 835 for bivalent cohorts against BA.5; appendix p 8 ), consistent with findings published in 2023. 5 There was no discernible waning of antibody responses in the BA.5 breakthrough infection cases over the same observation period. This finding suggests that our vaccine cohorts were not affected by undetected breakthrough infections.…”
mentioning
confidence: 81%